Application of virtual reality in teleoperation of the military mobile robotic system TAROS. (9th January 2018) - Kot, Tomáš; Novák, Petr
The article presents some aspects of a complex control system of a teleoperated military mobile robot Tactical Robotic System (TAROS) related to virtual reality and assistance to a human operator in general. Described is especially the unique and innovative system of virtual operator station which uses the HMD Oculus Rift to put the operator into a virtual space containing visual feedback from the robot and camera images, including stereovision. The virtual operator station serves as a cost-effective and portable replacement of what otherwise would be a large room with expensive equipment. Mentioned is also another system that helps the operator with remote manipulation tasks – the anti-collision system preventing damage done to the mechanical parts of the robot by incautious movements of the manipulator arm.